Design of low-power PVT-aware circuits for power management applications - Wang, Dong (2018)
In recent electronics industry, power management plays a significant role to extend the battery life of battery-powered portable electronic devices. Due to the push for low-power CMOS circuits, the power-aware design agenda will be addressed in the power management circuits. Besides, turning to sub-90nm CMOS technologies in System-on-Chip (SoC) environment, the performances are often significantly influenced by process, supply voltage and temperature (PVT) variations. These two key issues impose design challenges to circuits that are able to sustain the targeted specifications and to provide good fabrication yield. To tackle the stated problems, this work aims to explore the research, design, analysis and implementation of low-power PVT-aware circuits for power management applications in advanced nanometer CMOS technologies. In an exemplary application of a smart power system that the supply voltage can be a function of device’s threshold voltage (VTH) to counteract the process variation, a threshold voltage reference circuit is often needed in the design. This thesis will present the MOSFET VTH reference circuit that employs a dual-segment nonlinear temperature compensation method to provide thermal stability. Besides, the supply insensitivity is another key design parameter to be addressed in this work. The measured results have indicated that the VTH reference circuit yields a T.C. of 28.7 ppm/oC, power supply rejection (PSR) of -43.5 dB at 10 MHz and line sensitivity of 70.8 ppm/V. The performance metrics are better than those of reported works. In another circuit of the above power system, it requires a stable current source. This work presents a new current source architecture which is the embodiment of a process-tolerant bias current circuit and a scaled process-tracking bias voltage source for the dedicated temperature-compensated voltage-to-current (VI) conversion. The measurement results have shown that the current source consumes a quiescent power of 7.18 μW whilst achieving a sensitivity figure-of-merit (FOM) of 2.34% in terms of total PVT variation. Such the low-power low-sensitive features are better than most of the reported works and comparable with the state of art. On top of that, there exists another challenge from the non-ideal CMOS stress effect that causes the performance degradation in the PVT-aware circuits. In this work, a new electrical model is proposed to predict the stress effect that impacts on the electrical performance of reference circuits. It has validated that there is a reasonable correlation between the model prediction results and the measurement results of the above stated voltage and current reference circuits. Of particular noted, this is the first electrical model that addresses the impact of stress effect on the reference circuit designs in the field. In the low-dropout (LDO) regulator dedicated to power management applications where low power, low voltage, low transient spike and sustainability of transient metrics are concerned, the circuit techniques are the major focus of this work. First, a new low-voltage transient-assisted embedded driving stage (TAEDS) with low-output impedance is presented. This aims to enhance the slew rate at the gate of power transistor whilst allowing low quiescent current under low supply design. Second, the transient-assisted technique together with the multiple feedback circuit topology, process-temperature (PT) aware power transistor biasing network and the aforementioned constant current source architecture are then applied to realize a low-power PT-aware LDO regulator in 40nm CMOS technology. This results in the performance-aware regulator which can sustain low undershoot/overshoot effect, reduce speed degradation, maintain good stability and eliminate the circuit trimming in the context of total process and temperature variation under low-quiescent power constraint. The measurement results have confirmed the circuit operation for a full load current of 100 mA at a parasitic capacitive load of 100 pF under a 0.75 V supply. Based on the measured results from 12 samples, the regulator consumes an average quiescent power of 19.5 μW whilst an average settling time of 414 ns during full load current step transitions at room temperature. The average load transient voltage variation is 23.9 mV and the regulator achieves an average transient FOM value of 12.6 mV, which is better or comparable than most of the published output capacitor-less (OCL) LDO counterparts. The process corner simulations as well as the measurement results under temperature corners have validated the regulator’s sustainable transient performance metrics under process and temperature variations.